Different ways of recounting a session: therapist reconstructions and verbatim transcripts. Implications for training and understanding of the process in two cases of gender violence - Mantilla Lagos, Carla (2024)
The reconstruction of psychoanalytic sessions from the therapist’s subjective record has been the paradigmatic input from which therapeutic processes have been studied and the main theoretical and technical psychoanalytic models have been developed, being central material in the training of therapists. The systematic investigation of the therapeutic process from audio and video recordings, as well as the direct observation of caregiver-infant dyads for studying the forms of communication and mutual regulation, have generated a broadening of the understanding of the processes responsible for psychological change and the development of competencies for clinical work. Thus, we proposed to analyze the reconstructions that two therapists made of psychotherapy sessions with women victims of violence, along with the literal transcriptions of these sessions (audio recorded), with the aim of analyzing how these two ways of recording the session are related, in order to understand relevant aspects of the collection and recording of the therapeutic process, and to discuss their implications in therapeutic training, particularly in the work with victims of gender violence. This is a qualitative approach and the data was analyzed through an inductive thematic analysis method (Braun & Clarke, 2006). The results show common elements and significant differences between both records, which were organized into three thematic axes: (1) the similar, (2) the attenuated, and (3) the excluded. In the similar, the reconstructions are linked to the transcriptions insofar as they maintain a sequential organization of the main events narrated and the textual register of phrases, metaphors and figurative contents. On the other hand, contents associated with aggression, violence, sexuality and affective aspects, especially those expressed towards the therapist or those of high intensity, are recorded in the reconstructions in an attenuated and softened form. Likewise, the nonverbal, prosodic or rhythmic interactional aspects that organize the therapeutic exchange are omitted in the reconstructions. We discuss the reliance on the therapist’s reconstructions as the only record for purposes of therapeutic supervision and understanding of the processes, particularly in cases of gender-based violence.